Did Our Species Evolve in Subdivided Populations across Africa, and Why Does It Matter?. (August 2018) - Scerri, Eleanor M.L.; Thomas, Mark G.; Manica, Andrea; Gunz, Philipp; Stock, Jay T.; Stringer, Chris; Grove, Matt; Groucutt, Huw S.; Timmermann, Axel; Rightmire, G. Philip; d'Errico, Francesco; Tryon, Christian A.; et al.
Abstract : We challenge the view that our species, Homo sapiens, evolved within a single population and/or region of Africa. The chronology and physical diversity of Pleistocene human fossils suggest that morphologically varied populations pertaining to the H. sapiens clade lived throughout Africa. Similarly, the African archaeological record demonstrates the polycentric origin and persistence of regionally distinct Pleistocene material culture in a variety of paleoecological settings. Genetic studies also indicate that present-day population structure within Africa extends to deep times, paralleling a paleoenvironmental record of shifting and fractured habitable zones. We argue that these fields support an emerging view of a highly structured African prehistory that should be considered in human evolutionary inferences, prompting new interpretations, questions, and interdisciplinary research directions. Highlights: The view that Homo sapiens evolved from a single region/population within Africa has been given primacy in studies of human evolution. However, developments across multiple fields show that relevant data are no longer consistent with this view. We argue instead that Homo sapiens evolved within a set of interlinked groups living across Africa, whose connectivity changed through time. Genetic models therefore need to incorporate a more complex view of ancient migration and divergence in Africa. We summarize this new framework emphasizing population structure, outline how this changes our understanding of human evolution, and identify new research directions.